Response of Bud Banks of a Freshwater Herbaceous Marsh Plant (Glyceria Spiculosa) to Heterogeneous Habitat: Field Observations and Experiment - Mengdie Zhou; Changwei Zhang; Xianglong Jin; Qiyao Zhang; Peng Zhang; Anni Bao; Yanjing Lou (Ecology and Evolution, 2025)
ABSTRACT Exploring plant adaptation strategies under habitat variations from the perspective of bud banks is essential for understanding vegetation regeneration under global changes. However, the response of wetland plant bud banks to combined water and nutrient fluctuations remains unclear. In this study, field surveys across three vegetation zones (wet meadow, tussock marsh, and marsh) and pot experiments with three flooding periods (no flooding, flooding for 1–5 weeks, and flooding for 6–10 weeks), four nitrogen levels (1, 10, 30, and 100 mg/L) and two nitrogen forms (ammonium and nitrate) of Glyceria spiculosa bud banks were conducted. Our results showed that rhizome internode buds (accounting for 91%) dominated the bud bank compared with rhizome apical and tiller buds in natural habitats, and bud density in marsh (2475.64 No./m2) was higher than that in tussock marsh (1225.33 No./m2) and wet meadow (1583.43 No./m2). In the pot experiment, the proportion of tiller buds exceeds that of rhizome internode buds. The densities of total buds and tiller buds increased with increasing nitrogen levels, and the effect of ammonium nitrogen is higher than that of nitrate nitrogen. Overall, the impact of nitrogen is greater than that of flooding. These findings reveal that adjusting bud bank composition and density is a core adaptive strategy of wetland clonal plants to adapt to changing environmental conditions. Meanwhile, management and regulation of nitrogen fertilizers (including nitrogen form and level) and flooding periods should be paid more attention to in wetland restoration to maintain bud bank‐mediated regeneration capacity of plant populations.